Study on qualitative analysis in cosmetic takaout plant by multivariate statistical - Ait Sidi Mou, abdelaziz; E. Ghanjaoui, E.; Daoudi, M.; El Gamany, B. (International Journal of Advanced Chemistry, 2020)
This study examines the distributions and behavior of trace elements in five takaout plant samples. Multivariate statistical methods involving principal component analysis and hierarchical cluster analysis are applied. The measurements were performed using 21 elements (Al, B, Ba, Ca, Co, Cr, Cu, Er, Fe, K, La, Mg, Mn, Na, Ni, Sc, Sr, Ti, Y, Yb, Zn) at µg g-1 level determined by ICP-OES. The coefficients calculated for samples indicated a poorly negative correlation between the trace elements and Pr. A strong positive correlations among K, Na, Ca, Mg, Fe, Al, Sr, Ti, Er and Cr show a similarity in their change rules. Also, negative correlations between K and Na with Mn, Zn and Ba were showed, which indicates that these elements haven’t a similarity in their behaviors, the increase of one (K and Na) conducting of decrease of others (Mn, Zn and Ba). The correlation matrix shows that Cr has good consistency with the trace elements in the sample. In particular, the correlation coefficient with Mg followed by Sr, Ca, and Fe correlations. These strong correlations between these variables show the similarity of the phenomena at the origin in takaout plant.